The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1038/jid.2011.377
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ, IL-21, and IL-10 Co-Expression in Evolving Autoimmune Vitiligo Lesions of Smyth Line Chickens

Abstract: The Smyth line (SL) of chicken is an excellent animal model for human autoimmune vitiligo. In SL vitiligo (SLV) post-natal loss of melanocytes in feathers appears to be due to cell-mediated immunity. In this study, leukocyte-infiltration and associated expression (RNA) of immune function-related cytokines in growing feathers were investigated throughout SLV-development and -progression. Both leukocyte infiltration and cytokine expression levels started to increase near visible SLV onset (early SLV), reached pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 41 publications
8
57
0
2
Order By: Relevance
“…inflammatory response and immunological disease) (Figure 1 and 2). DE genes of both T and B cell markers (Table 1 and 2) and functions of humoral and cell-mediated immune response (Figure 1 and 2) in the current study are in line with previous studies demonstrating involvement of both types of immune responses in melanocyte loss in the etiology of SLV [6,10,12,16]. Furthermore, it appears that the humoral immune response was particularly important in early SLV development, since DE genes in EV samples were significantly (1 st network) associated with this function (Figure 2).…”
Section: Discussionsupporting
confidence: 92%
“…inflammatory response and immunological disease) (Figure 1 and 2). DE genes of both T and B cell markers (Table 1 and 2) and functions of humoral and cell-mediated immune response (Figure 1 and 2) in the current study are in line with previous studies demonstrating involvement of both types of immune responses in melanocyte loss in the etiology of SLV [6,10,12,16]. Furthermore, it appears that the humoral immune response was particularly important in early SLV development, since DE genes in EV samples were significantly (1 st network) associated with this function (Figure 2).…”
Section: Discussionsupporting
confidence: 92%
“…Studies of Smyth line chickens, an animal model for human autoimmune vitiligo, have demonstrated that elevated leukocyte infiltration in early and active vitiligo is accompanied by increased levels of cytokine expression, especially in interferon (IFN)-IL-10, and IL-21 [68]. Recently, in a mouse model of spontaneous melanoma, Treg cell-depletion and IL-10 neutralisation led to an increased occurrence of vitiligo which correlated with a decreased incidence of melanoma metastases [69].…”
Section: Interleukin-10mentioning
confidence: 99%
“…4,18,19) In vitiligo patients and animal models, IFN-γ level is significantly elevated in lesional skin. 4,20) IFN-γ signaling regulates the expression of cytokine as well as adhesion molecules facilitating the lymphocyte migration. 16,21) So that, local IFN-γ release promotes further recruitment of melanocyte-specific CD8+ T cells into the vitiligo lesion.…”
Section: Egcg Inhibited Janus Kinase (Jak)2 Activity In Vitromentioning
confidence: 99%